Multicomponent approach reveals differences in affective responses among children and adolescents - Kseniia Konopkina; Hilla Hirvaskoski; Jari K. Hietanen; Heini Saarimäki (Scientific Reports)
Abstract Investigating age-related shifts in affective responses to emotionally salient stimuli is key to comprehending emotional development during childhood and adolescence. Most of the research regarding emotional experiences has focused on adults, while the understanding of the development of emotional experiences across childhood remains elusive. To address this gap, we explored whether physiological and behavioural responses as well as self-reported emotions elicited in children and adolescents by naturalistic stimuli differ from those in adults. We developed a set of emotional videos to elicit different emotions – fear, joy, anger, sadness, amusement, and tenderness - and measured emotional intensity ratings, electrocardiography, and eye movements from 8–15-year-old children and adults during the viewing of the videos. We identified age-related changes in all measured responses. Emotional intensity and behavioural responses varied across emotion categories. Furthermore, specific emotions showed different maturation patterns. The study highlights the importance of a multicomponent approach to accurately discern and understand emotional states.